2023
DOI: 10.3389/fenvs.2022.1082713
|View full text |Cite
|
Sign up to set email alerts
|

Variations in precipitation and temperature in Xinjiang (Northwest China) and their connection to atmospheric circulation

Abstract: As one of the most vulnerable types of global ecosystems and water resource systems, arid regions are most sensitive to climate change. The Xinjiang (XJ) region is an important part of the arid region in Central Asia and is representative of global arid regions. The complex topography and underlying surface result in distinct climate change characteristics in XJ. In this study, XJ was divided into five sub-regions: the Irtysh River Basin (IRB), the economic belt on the northern slope of the Tianshan Mountains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, A. alternata ’s diameter increased at 120 °C, indicating that the activity of the crude lipopeptides was unaffected by different heat treatments below this temperature ( Figure 2 a). The unstable climate change may affect the levels of A. alternata and mycotoxins in tomatoes [ 36 ]; thus, the stable lipopeptides might a good choice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, A. alternata ’s diameter increased at 120 °C, indicating that the activity of the crude lipopeptides was unaffected by different heat treatments below this temperature ( Figure 2 a). The unstable climate change may affect the levels of A. alternata and mycotoxins in tomatoes [ 36 ]; thus, the stable lipopeptides might a good choice.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal stability results showed that the diameter of A. alternata did not change after the incubation of crude lipopeptides treated at 25 • C and 60 • C. However, A. alternata's diameter increased at 120 • C, indicating that the activity of the crude lipopeptides was unaffected by different heat treatments below this temperature (Figure 2a). The unstable climate change may affect the levels of A. alternata and mycotoxins in tomatoes [36]; thus, the stable lipopeptides might a good choice.…”
Section: Stability Test Of Anti-fungal Activity Of Crude Lipopeptidesmentioning
confidence: 99%
“…The MK test and SS method are commonly used for trend analysis of precipitation and temperature (Benjamin L Saitluanga et al, 2021;F N. Kilonzo, 2022;Mohammad Shad et al, 2022;Deepak Tiwari et al, 2021;Mohammed Mainuddin et al, 2022;Rohit Mann et al, 2023;Nutthakarn Phumkokrux et al, 2022;Abdur Rohman et al, 2022;Tagele Mossie Aschale et al, 2023;Guixiang Zhou et al, 2023). These methods allow for the detection of monotonic trends and the estimation of trend magnitudes (F N. Kilonzo, 2022;Mohammad Shad et al, 2022;Rohit Mann et al, 2023).…”
Section: Statistical Testsmentioning
confidence: 99%
“…SS estimator is commonly used to estimate the magnitude of changes in variables, such as streamflow (Ali et al, 2019) and precipitation (Tayyab et al, 2019). Wavelet analysis has been used to identify the periodicity of streamflow (Chang et al, 2018) and to analyze the interrelationship among temperature, precipitation, and atmospheric circulation indices (Guixiang Zhou et al, 2023). The regional MK test, on the other hand, is used to assess consistent trends across multiple sampling points within a region (Fang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%